Rekomendasi Penataan dan Perawatan Batu Nisan Kuno Berbasis Lingkungan di Gampong Pande, Banda Aceh - Butar Butar, Masnauli; Nazli; Meilina, Hesti (PURBAWIDYA, 2024)
In Gampong Pande there are cultural heritage objects and mangrove forests which are the part of former ancient port city of the Aceh Darussalam Kingdom. After the earthquake and tsunami waves that hit the coast of the city of Banda Aceh in 2004, the former capital city was damaged so ecological recommendations for the arrangement and maintenance of cultural heritage objects are needed. This paper aims to provide recommendations for the arrangement and care of ancient tombstone cultural heritage objects. The methods used were literature studies, initial surveys, observations, aerial photographs, satellite images, tombstone object distribution maps, object plan recommendations, lichen sample tests in the laboratory, and field tests of citronella and coconut oil essential oil emulsions. Recommendations are planned for arranging ancient tombstones located in scattered fish ponds and mangrove forests and planning supporting facilities for their protection, development, and utilization. In maintaining ancient tombstones, environmentally friendly materials were tested, namely an emulsion of citronella essential oil, distilled water, and coconut oil. Variations in citronella essential oil emulsion with distilled water are 0%, 10%, 20%, 30%, 40%, and 100% and coconut oil concentration is 100%. Observations were made on color changes visually and with a microscope for 24 hours, 48 ​​hours, and 72 hours. Test results on six variations after the specified time both in the field and laboratory tests showed that citronella essential oil could inhibit the growth of lichens while coconut oil was not effective.